Skill-specific competitive process designs in rugby union - Mavrina, S. B.; Ivanov, V. A.; Kruglova, J. V.; Nosov, S. M.; Nosova, A. V. (Theory and Practice of Physical Culture, 2017)
The article considers some issues of importance for the competitive process design in the Rugby Union competitions. Based on analyses of the competitive records of rugby players versus their qualifications, the authors offered an isomorphic element of game process. The standard element includes a few constituents dominated by the "game moments" and "rearrangement intervals". The elementary game constituents were classified based on the statistical analyses of the data indicative of the skill-specific competitive game designs for highly-skilled and elite rugby players.